Pyrolysis Characteristics of Hailar Lignite in the Presence of Polyvinyl Chloride: Products Distribution and Chlorine Migration - Hui Fan; Menglin Ren; Caiyun Feng; Yue Jiao; Yonghui Bai; Qingxiang Ma (Energies, 2022)
This study investigated the effects of polyvinyl chloride (PVC) addition on low-rank coal’s pyrolysis characteristics, especially the products distribution and chlorine migration. Hailar lignite (HLE) with different industrial, pure, PVC-content additions were prepared (the mass percentage of PVC addition was from 5% to 25%), and the co-pyrolysis characteristics of HLE and PVC were performed on a fixed-bed reactor and thermogravimetric analyzer. The chars were characterized with X-ray diffraction (XRD), X-ray fluorescence (XRF), and Fourier-transform infrared (FT-IR) spectroscopy analysis. The gas and tar compositions were analyzed by using gas chromatography (GC) and a gas chromatography–mass spectrometry (GC–MS) system, respectively. The results indicate that the addition of PVC can increase the release amounts of CH4, C2H4, and C2H6, simultaneously reducing the release amount of CO2 and CO; the quality of pyrolysis tar was also improved, especially the alkane content in tar, which increased by 6.9%. The migration of chlorine in PVC was analyzed with the different PVC additions and terminal pyrolysis temperatures. It showed that the content of chlorine in the gas phase first increased with the increasing pyrolysis temperature, but at the terminal temperature of 600 °C, the chlorine in the gas phase began to decrease. The results of the co-pyrolysis char characterization show that the content of the alkali metal oxide gradually decreases in the char, and metal chloride appears during the pyrolysis process. In the co-pyrolysis reaction of coal and PVC, chlorine was fixed in the char, thereby reducing the distribution of chlorine in the gas phase. This also proves that the PVC pyrolysis process, with the participation of low-rank coal, can enrich chlorine into the solid phase, thus reducing the emission of chlorine in the gas phase.